Validation and clinical performance of a single test, DNA based endometrial cancer molecular classifier - Jamieson, Amy; Grube, Marcel; Kommoss, Felix; Lum, Amy; Leung, Samuel; Chiu, Derek; Henderson, Gabriel; Heitz, Florian; Heublein, Sabine; Zeimet, A G; Hasenburg, Annette; Diebold, Joachim; et al. (International journal of gynecological cancer, 2024)
Objectives - We have previously shown that DNA based, single test molecular classification by next generation sequencing (NGS) (Proactive Molecular risk classifier for Endometrial cancer (ProMisE) NGS) is highly concordant with the original ProMisE classifier and maintains prognostic value in endometrial cancer. Our aim was to validate ProMisE NGS in an independent cohort and assess the performance of ProMisE NGS in real world clinical practice to address if there were any practical challenges or learning points for implementation. - Methods - We evaluated DNA extracted from an external research cohort of 211 endometrial cancer cases diagnosed in 2016 from Germany, Switzerland, and Austria, across seven European centers, comparing standard molecular classification (NGS for POLE status, immunohistochemistry for mismatch repair and p53) with ProMisE NGS (NGS for POLE and TP53, microsatellite instability assay) for concordance metrics and Kaplan-Meier survival statistics across molecular subtypes. In parallel, we assessed all patients who had undergone a new NGS based molecular classification test (n=334) comparing molecular subtype assignment with the original ProMisE classifier. - Results - A total of 545 endometrial cancers were compared. Prognostic differences in progression free, disease specific, and overall survival between the four molecular subtypes were observed for the NGS classifier, recapitulating the survival curves of original ProMisE. In 28 of 545 (5%) discordant cases (8/211 (4%) in the validation set, 20/334 (6%) in the real world cohort), molecular subtype was able to be definitively assigned in all, based on review of the histopathological features and/or additional immunohistochemistry. DNA based molecular classification identified twice as many ‘multiple classifier’ endometrial cancers; 37 of 545 (7%) compared with 20 of 545 (4%) with original ProMisE. - Conclusion - External validation confirmed that single test, DNA based molecular classification was highly concordant (95%) with original ProMisE classification, with prognostic value maintained, representing an acceptable alternative for clinical practice. Careful consideration of reasons for discordance and knowledge of how to correctly assign multiple classifier endometrial cancers is imperative for implementation.
Gesehen am 23.05.2025